2015
DOI: 10.1155/2015/849647
|View full text |Cite
|
Sign up to set email alerts
|

The Effect ofChanna striatus(Haruan) Extract on Pain and Wound Healing of Post-Lower Segment Caesarean Section Women

Abstract: Channa striatus has been consumed for decades as a remedy to promote wound healing by women during postpartum period. The objectives of this study were to compare postoperative pain, wound healing based on wound evaluation scale (WES), wound cosmetic appearance based on visual analogue scale (VAS) scores and patient satisfaction score (PSS), and safety profiles between C. striatus group and placebo group after six weeks of lower segment caesarean section (LSCS) delivery. A randomised, double-blind, placebo-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…This was due to the presence of compound compounds in Snakehead fish extract so that more nutrients are needed during the wound healing period. Snakehead fish extract contains compounds that are important for the process of tissue synthesis and wound healing, such as albumin, minerals Zn, Cu, and Fe (Ab Wahab et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the presence of compound compounds in Snakehead fish extract so that more nutrients are needed during the wound healing period. Snakehead fish extract contains compounds that are important for the process of tissue synthesis and wound healing, such as albumin, minerals Zn, Cu, and Fe (Ab Wahab et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Ruptur perineum was the second leading cause of post partum haemorragi after uterine atony that occurs in almost the first giving birth and not infrequently also in subsequent labor (Sharma & Parashar, 2012). Snakehead fish have compounds that are important for the body, such as proteins and some minerals (Ab Wahab et al, 2015). The protein content of Snakehead fish reaches 25.5% compared to other fish proteins, Snakehead fish albumin is quite high reaching 6.22% and Snakehead fish meat contains zinc minerals with levels of 1.74 mg / 100 grams (Fajri, Hadisaputro, & Soejoenoes, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown many functions in the cell membrane for blood clothing 5 , wound healing and antinociceptive activities of snakehead fish. 11 Besides, four preliminary studies have reported that snakehead fish extract has potent antiinflammatory property [12][13][14][15][16] but to the best of our knowledge, no research was done to study the effect of snakehead fish aqueous extract in lipid base nanocarrier for inflammation and cancer. For parenteral administration of drugs that might be targeted to specific cells, small particulate carriers are required.…”
Section: Introductionmentioning
confidence: 99%
“…Pengaruh frekuensi pemberian Moina sp. sebagai pakan awal pada ..... (Adang Saputra) PENDAHULUAN Ikan gabus Channa striata termasuk ikan air tawar yang mempunyai nilai ekonomis tinggi sebagai ikan konsumsi dalam bentuk segar maupun olahan (Kusmini et al, 2016), serta kandungan albuminnya yang mampu mempercepat proses penyembuhan luka setelah proses operasi (Wahab et al, 2015). Tingginya tingkat kematian selama stadia larva menjadi kendala dalam pengembangan budidaya ikan gabus (Amornsakun et al, 2011).…”
unclassified